Monitoramento do processo de recuperação de um solo aluvial sódico em condições de drenagem subterrânea - Soares, Osvaldo Hélio Dantas (1996)
With the objective to analyses the evolution of physical and chemical parameters in an alluvial alkaline soil in process of reclamation and evaluate the drainage system, a research was conducted from August 1995 to January 1996 in the Curu Valley Experimental Station at Pentecoste-Ce. Sample from the soil, irrigation water and drainage water (from the drains and from holes in the soil profile) were analyzed and related with data obtained in 1988, when the system was tested. The results of these analyses show the soil characteristics have changed, with decrease in pH, and increase in Electrical Conductivity (EC) in the entire soil profile studied. In addition, the saturated hydraulic conductivity increased as a result of the decrease in the Exchangeable Sodium Percentage (ESP), what made the soil be classified as normal, according to its salinity and alkalinity. The chemical analyses of the drainage water show variation in the EC, Sodium Adsorption Ratio (SAR), pH, soluble ions concentration, and in its level of salinity and alkalinity, with increase in its quality. The subsurface drainage system, previously installed at two different depths, was built of clay pipes 0.30 m long, with lateral drains 125.0 m long and spaced at 17.5 m from each other. The envelope was built using two 0.10 m layer of gravel and coarse sand. To evaluate the drain discharge it was used the volumetric method. With the values of hydraulic head and discharge from the drain, the reaction factor, saturated hydraulic conductivity, transmissivity and drainage porosity were calculated. Having been a parameter used in the calculation of the drain spacing, the saturated hydraulic conductivity was also estimated throughout the Auger-Hole method, having been given emphasis to the spatial variability of this parameter. In the evaluation of the drainage performance, it was found a value of 4.3 days.m-1 to the entry resistance factor, what shows that the system was not working properly. This performance may be associated with the soil hydraulic characteristics, age of the drainage system (10 years old), clogging of the pipes (specially in the connections), non-uniformity of the envelope, and mis-alignment of the pipes. The results also show that the water table flows towards the drains, what shows the importance of this drainage system. It was also found that the Glover-Dumm approach best estimated the drain spacing